A review of meta-analytic research in accounting. Issue 1 (October 2015) - Khlif, Hichem; Chalmers, Keryn
Abstract: This study reviews the use of meta-analysis in accounting research. We categorize the meta-analytic research into five topics: financial reporting, auditing, corporate governance and accounting quality, management accounting, and miscellaneous topics. Further, we classify the studies by the meta-analysis technique employed:Hunter et al. (1982), Hunter and Schmidt (2000), Lipsey and Wilson (2001), and Stouffer's approach. We identify 27 meta-analytical studies over the period 1985–2014 with financial reporting (auditing) topics representing seven (six) of these studies. Our review highlights that meta-analytic methods are being applied and accepted, more frequently, to answer complex questions concerning the moderating effects of country-level variables, such as national culture, economic conditions, and institutional characteristics, on various associations of interest.